The impact of knowledge management on organizational performance / Muhammad Amirul Amri Abdul Talib - Abdul Talib, Muhammad Amirul Amri (Faculty of Business Management, 2017)
Organizational performance is an important topic to be studied either by researchers or organizations. Some organizations have several factors affecting the performance of their company. This study aims to explore the factors that affect organizational performance among organizations that are based in Malaysia through MEEC MATRADE directory. The researcher chose to use three independent variables that may affect organizational performance which are knowledge, information technology, and organization. Questionnaires were distributed to 441 organizations as the appropriate sample size is 226. This is to be safe when eliminating foul questionnaires from the respondents (if any). The researcher chose simple random sampling techniques for this study. All the quantitative data obtained from this research study were analyzed by the Statistical Package for the Social Sciences Software (SPSS) version 20. The results from this study including the conclusions and recommendations will help future researchers to explore the factors of organizational effectiveness in more detailed and accuracy.